1.2x-0.5x=6.
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 17:54:00
1.2x-0.5x=6.1.2x-0.5x=6.1.2x-0.5x=6.
1.2x-0.5x=6.
1.2x-0.5x=6.
1.2x-0.5x=6.
1.2x-0.5x=6.
0.8X-0.5*1.2X=10
(X+X)+(X-X)+(X*X)+(X/X)=100
0.5X+120+0.3X=X
4X+0.5X=13.5X
x-30-0.2x=0.5x
x-0.3x-0.5x=20
9x+0.5x+x=
0.5X=6.
4x一5/0.5—5x-0.8/0.2=1.2-x/0.1 x=
X+0.5X=3 X-0.8X=8
求x:|x|-|x-4|=0.5x-1
65%X+X=6.
8x-5.5x=7.57.2x÷3.6=2 3x+6x-8x=0.7 12x-2x-5x=4.512x-x=0 5x+x=1.8 3.2x+1.8x=64.8x-0.8x=6 6.3-0.3x=9.6 8.6x-8.5x=0.720x-2x=36 9x+6x=4.5 18x-12x=5.42x-1.6x=3.6 18x+3x=7×6 1.2x-0.5x=0.71.3x+2.7x=1 4x-3.2x=6.4 0.8x+3.2x+3x=562.8x-2x=7.2
1.2x=x+20
1.2X-30=X
1.2x-x=0.
x-1.2x=9.6